Sharp convex bounds on the aggregate sums: An alternative proof - Chuancun Yin; Dan Zhu (Risks, 2016)
It is well known that a random vector with given marginals is comonotonic if and only if it has the largest convex sum, and that a random vector with given marginals (under an additional condition) is mutually exclusive if and only if it has the minimal convex sum. This paper provides an alternative proof of these two results using the theories of distortion risk measure and expected utility.
Keywords: 330; comonotonicity; convex order; distortion risk measure; mutual exclusivity; stop-loss order